Salbutamol toxicity in a Golden Retriever dog- A case report - kasaraneni, Saikrishna; K. Jeyaraja; Yamini thakur; V. Arun (Indian Journal of Veterinary Medicine, 2024)
Salbutamol is a beta2 adrenergic agonist commonly used in human and veterinary practice. Toxicity due to salbutamol is uncommon and if happened its therapeutic management is important to prevent lethal consequences. Three year old Golden retriever was presented to the hospital with accidental consumption of salbutamol tablets. On clinical examination dog was dull, tachycardic and having tachypnoea. Serum biochemical examination revealed severe hypokalemia and sinus tachycardia on electrocardiography. Fluid therapy was initiated along with intravenous potassium and oral beta blocker propranolol. Significant clinical recovery was noticed by 24 hours of therapy.